(untitled) (Advancements in Homeopathic Research, 2022)
Skin is the largest organ of body and considered most difficult organ to be treated, as there is no cure for eczema and no effective conventional therapy, many types of treatment are available to treat skin disease in different system of medicine allopathic, ayurveda or can be surgical but none of them is fully satisfactory. Homoeopathy offers very soothing and effective treatment for cases which are difficult to manage by modern medicine and which have relapse after stoppage of treatment. Here we are presenting a case of dry eczema, which failed to respond to modern medicine and was mange very well by homeopathy with, in short time of period without any relapse after stoppage of treatment.